A comparative clinical study between intra-caesarean and interval intra uterine copper device insertion in caesarean deliveries - R., Geetha Lakshmi; S., Sornam M.; G., Thenmozhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Health and family welfare of Indian Ministry, emphasis on postpartum IUCD insertion. Here we conducted a clinical study comparing intra-caesarean and interval CuT-380A insertion in caesarean deliveries. Methods: A systematic study with 150 patients in each group, recruited clients alternately. Group A Intra-Caesarean Cu-T insertion and Group B Interval Cu-T insertion in caesarean deliveries. Groups were followed up at 6th week and 6th month post insertion with a set of parameters. Missed strings, expulsion and infection rates were the primary outcome measures. Results: Infection rate is higher in Group A (2.3%) at 6th week, and at 6th month infection rate is higher in Group B (1.8%). Missed strings are higher in intra-caesarean than in interval insertion method both at 6th week and 6th month follow up p=0.000, hence significant. Expulsion rate is higher in Group A (2.5%) at 6th week, and at 6th month expulsion rate is higher in Group B (1.9%). There are no complications such as uterine perforation or contraceptive failures in both the groups during the study period. By analysis, there are no significant differences in infection and expulsion rates between the groups. For missed strings there is significant difference between the groups with more missed strings in intra-caesarean insertion method. Conclusions: To conclude, intra-caesarean method is equally effective as interval IUCD insertion method without added complications in caesarean deliveries, with advantage of high motivation, good compliance, safety and ease for the provider to deliver services.